Challenges and prospects of continuous assessment implementation in rural schools in Nigeria: the teachers' perspective (2012)
This study examined some challenges and prospects of implementating Continous Assessment (CA) in the Nigerian rural schools, using schools in two rural Ibadan local govenrment areas of Egbeda and Lagelu of Oyo state, Nigeria as case study. It utilized survey research procedure while the study data was collected ex post facto. Fifty-six teachers were sampled from five schools and used as subjects in the study. One instrument was used to collect data which were analysed using percentages and chi-square statistic. Findings show that challenges of implementing CA in rural Nigerian schools include: lack of good and enabling environment, dilapidated classes, lack of relevant equipment for its execution, shared interest between farming and devotion to school work on th part of the teachers who are the chief implementaters, lack of knowledge and skills of the appropriate evaluation techniques, etc. Respondents suggested that time should be given to implimenting CA, teachers should be adequatly trained in the techniques of evaluation, relevant modern technology for its conducts and recording should be provided for teachers.It was discovered that these rural Nigerians do not understand the import of CA implementation. It was recommended that teachers should be given relevant training on modern evaluation techniques, funds be available for the purchase of environment should be provided by way of acquisiton of relevant infrastructure and facilities